The strength training anatomy workout III advanced programming for serious strength and power - Delavier, Frederic; Gundill, Michael (Human Kinetics, 2018)
Books by best-selling author Frederic Delavier have sold more than two million copies. His latest, The Strength Training Anatomy Workout III, is an advanced guide to the secrets of training. It will help you cross the plateau to achieve greater muscle development and gains